Optimization of Fish Oil Sardinella lemuru from Canning Industry by Products - Rodiah Nurbaya Sari; Bagus Sediadi Bandol Utomo; Jamal Basmal; Rinta Kusumawati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
Fish oil could be extrated from lemuru (Sardinella lemuru) or lemuru canning industry byproducts. The fish oil should be refined first before using as omega-3 sources. This reasearchobtained was purification of fish oil from lemuru canning industry by products at Bali usingvariations purification method. The fisrt step was done by analysis of crude oil such of free fattyacids value, peroxide value, and iodine value. Then after the purification process using variationspurification method, the refined fish oil was analyzed for same parametrs. The best refined fishoil was analyzed of composition fatty acid using gas chromatograph (GC) instrument. The resultshowed that the crude oil had free fatty acids value, peroxide value, and iodine value as follows24.03%; 6.97 meq/kg sample; 189.13 g/100 g sample. After the refining process using four methods,the result showed that free fatty acids value, peroxide value, and iodine value became: the firstmethod 24.02%; 6.16 meq/kg sample; 187.91 g/100 g sample. The second method 23.14%; 4.17meq/kg sample; 193.94 g/100 g sample. The third method 9.38%; 4.88 meq/kg sample; 225.39 g/100 g sample. And the fourth method 11.03%; 5.64 meq/kg sample; 222.69 g/100 g sample. Dueto the peroxide value, the refined lemuru oil that could met standard of Indonesian farmacope forconsumed fish oil was resulted from the third method. In the refined lemuru oil could be found ofEPA component (Methyl cis-5,8,11,14,17-Eicosapentaenoic acid methyl ester) with concentration650,65 μg/mL..Keywords: By products, fish oil, refining process, Sardinella lemuru